Prevalence of pathogenic and likely pathogenic variants in the RASopathy genes in patients who have had panel testing for cardiomyopathy. Issue 4 (14th February 2019) - Aljeaid, Deema; Sanchez, Ana Isabel; Wakefield, Emily; Chadwell, Sarah E.; Moore, Nicole; Prada, Carlos E.; Zhang, Wenying
Abstract : RASopathies are a group of developmental disorders caused by pathogenic variants in the RAS‐MAPK pathway. Cardiomyopathy is a major feature of this group of disorders, specifically hypertrophic cardiomyopathy (HCM). HCM can be the first presenting feature in individuals with RASopathies. We conducted a retrospective study of all individuals who have had a cardiomyopathy gene panel ordered through our institution to determine the prevalence of pathogenic or likely pathogenic variants in RAS pathway genes in individuals with cardiomyopathy. We evaluated variants in the following genes: BRAF, CBL, HRAS, KRAS, MAP2K1, MAP2K2, NF1, NRAS, PTPN11, RAF1, SHOC2, and SOS1 . We reviewed 74 cases with cardiomyopathy, including 32 with HCM, 24 with dilated cardiomyopathy (DCM), nine with both left ventricular noncompaction (LVNC) and DCM, four with LVNC only, two with arrhythmogenic right ventricular cardiomyopathy (ARVC) and three with unspecified cardiomyopathy. We identified four patients (5.41%) with pathogenic or likely pathogenic variants in HRAS, PTPN11 and RAF1 (two individuals). Indication for testing for all four individuals was HCM. The prevalence of pathogenic or likely pathogenic variants in RASopathy genes in our HCM patient cohort is 12.5% (4/32). We conclude that the RASopathy genes should be included on multi‐gene panels for cardiomyopathy to increase diagnostic yield for individuals with HCM.